What Determines Bond Market Development? New Theoretical Insights - Ameenullah Aman; Asmadi Mohamed Naim; Mohamad Yazid Isa (SEISENSE (PRIVATE) LIMITED, 2019)
Purpose- To diversify financing portfolio and reduce the reliance on the banking system, developing economies have realized the importance of bond market development. Bond markets facilitate economies to be more resilient towards the events of financial crises. Therefore, the share of the bond market in the financial system of the Asian economies has remarkably increased in the last decade. However, the academic literature on the bond market is very limited as compared to bank and equity markets. This was mainly because of the unavailability of vast data due to the absence of secondary markets for bonds in most of the economies. To fill this gap, this conceptual study postulates the theoretical relationships of bond market with various macroeconomic and financial factors. The study also assumes some new dimensions for bond financing and opens discussion for scholarly literature and empirical justifications. Design/Methodology- Content analysis approach is used to review relevant literature for the possible associations of the bond market with macroeconomic and financial factors. Practical Implications- The theoretical relationships discussed in the paper need empirical testing in future research to conclude policy implications. If the relationship between foreign capital and bond securities is established with empirical justification, we draw the policy that concerned authorities need to create a suitable environment for the attraction of foreign capital to provide support to the development of domestic debt market.